Articular cartilage reconstruction with TGF-β1-simulating self-assembling peptide hydrogel-based composite scaffold. (1st July 2022) - Ye, Weilong; Yang, Zhen; Cao, Fuyang; Li, Hao; Zhao, Tianyuan; Zhang, Huan; Zhang, Zhe; Yang, Shuhui; Zhu, Jinjin; Liu, Zhu; Zheng, Jingchuan; Liu, Huiying; et al.
Abstract: Transforming growth factor-β (TGF-β) is an important inducing factor for the differentiation of mesenchymal stem cells and the secretion of collagen II, but the inaccessibility and instability limit its application in clinical practice. In this study, the TGF-β1-simulating peptide LIANAK (CM) was connected with the self-assembling peptide Ac-(RADA)4 -CONH2 (RAD) to obtain the functionalized self-assembling peptide Ac-(RADA)4 -GG-LIANAK-CONH2 (RAD-CM). The results indicated that the CM-functionalized RAD hydrogel contributed to the enhanced expressions of chondrogenic genes and extracellular matrix deposition. The self-assembling peptides were then combined with decellularized cartilage extracellular matrix (DCM) to construct a composite scaffold for articular cartilage repair. The CM-functionalized composite scaffold RAD/RAD-CM/DCM (R/C/D) exhibited good bioactivity and structural stability and exhibited satisfactory performance in promoting neocartilage restoration and the reconstruction of the osteochondral unit. This study provides a promising strategy for in situ cartilage regeneration via the stable presentation of TGF-β1-simulating peptide. Statement of significance: Deficiency of effective chondrogenic inducers (especially, the TGF-β family) significantly limits the self-regeneration of cartilage in osteochondral defect cases. Oligopeptide LIANAK, named CM, could simulate TGF-β1's bioactivity with particular structure, but traditional chemical crosslinking to polymer scaffolds resulted in risks of safety and complication, which is unfavorable for clinical applications. Here, self-assembling peptide RAD was used to load CM, to obtain a TGF-β1 mimetic peptide hydrogel. Depending on the homology (amino acids) of RAD and CM, the synthesis of the whole peptide only needs simply extended sequences of CM following that of RAD by automated solid-phase peptide synthesis. The modified peptide effectively demonstrated osteochondrogenic bioactivity, ensured the convenience, safety, and mass production, which displayed great potential in tissue engineering research and translational medicine. Graphical abstract: Image, graphical abstract